2015
DOI: 10.1371/journal.pone.0125093
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘Self-Medication’ a Useful Term to Retrieve Related Publications in the Literature? A Systematic Exploration of Related Terms

Abstract: BackgroundSelf-Medication (SM), i.e. using medications to treat oneself, is a major concern for health researchers and policy makers. The terms “self medication” or “self-medication” (SM terms) have been used to explain various concepts while several terms have also been employed to define this practice. Hence, retrieving relevant publications would require exhaustive literature screening. So, we assessed the current situation of SM terms in the literature to improve the relevancy of search outcomes.MethodsIn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…WHO describes self-medication as the selection and use of drugs by the individuals themselves to treat the diseases or symptoms diagnosed themselves (6). Self-medication is a practice that is part of self-care where patients have a contribution to health-related decisions (7).…”
Section: Introductionmentioning
confidence: 99%
“…WHO describes self-medication as the selection and use of drugs by the individuals themselves to treat the diseases or symptoms diagnosed themselves (6). Self-medication is a practice that is part of self-care where patients have a contribution to health-related decisions (7).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 5b have revealed some of the most prominent and show similarities associated with utilize is pressed and chewed plant parts, with x 2 = 15.647, n = 50, df = 8, p-value = 0.0000. Chewing process is thought to be the activation mechanism of a plant secondary metabolite compound involving the enzyme present in saliva [13].…”
Section: Resultsmentioning
confidence: 99%
“…The term ethno-medication in many academic literatures has different meanings, such as causes of, diagnosis and treatment a disease as well as the level of health status. This, in turn provided ineffectiveness for reliable insight of relevant literature [12,13]. Several studies have suggested the fact that there are similarities in the selection of plant parts by animals and humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-medication, according to the World Health Organization, is the choice and use of medicines by people to treat self-recognized sicknesses or symptoms and is one part of self-care (1). It is the treatment of common health problems with products specifically designed and labeled to be used without medical supervision and approved as safe and effective for such use.…”
mentioning
confidence: 99%